MODERN ARCHITECTURE BOARD INFORMATION AND CONTROL SYSTEMS OF HEAVY VEHICLES - A. Z. Asanov (Российский технологический журнал)
The continuous increase in amounts of data processed on board of modern heavy trucks and complication of onboard systems and units functioning algorithms have led to the need to transfer the functions performed by a motorist to automatic robotized systems. Therefore, new solutions in the field of system architecture for on-board heavy truck information and control systems are required. The paper deals with the problems of information and control systems design for robotic heavy trucks control. In the paper the concept of hierarchies, functions and subsystems of control in complex ergatic systems like the control systems of modern heavy trucks as well as the control levels characteristic features have been considered. The concept for both the organization of information-measuring and executive systems in the form of mechatronic modules and adaptive correction mechanisms for vehicle movement control have been proposed.